Crisp-padhiar syndrome. Issue 2 (20th January 2011) - Crisp, TA; King, JB; Chan, O; Padhiar, N
Abstract : Introduction: The common cause of medial midfoot pain following acute trauma usually, either pronatory or inversion sprain is due to tibialis posterior tendon dysfunction, tibialis posterior tendinopathy, Os naviculare syndrome, stress fracture of the navicular and Lisfranc ligament injury. These are disabling conditions which are often treated in isolation. Crisp-Padhiar syndrome: We present a case history which highlights the complexity of the problem and discuss the findings of subsequent series of 42 patients who presented with post-traumatic medial midfoot pain. In Crisp-Padhiar syndrome patients present with combination of the following: (1) trauma, (2) presence of Os naviculare, (3) tibialis posterior tendinopathy, (4) tibialis posterior dysfunction, (5) acquired flatfoot, (6) Os naviculare synchondrosis and (7) anomalous tibialis posterior tendon attachment of Os naviculare. The treatment of choice in the initial stage is to stabilise the medial structures in Aircast Posterior Tibial Tendon Dysfunction brace for 6 weeks, followed by intensive physiotherapy and dependent on reduction of symptoms and degree of flat footedness, consider fluoroscopy guided tendon distension injection and introduction of customised carbon fibre foot orthoses. Surgery was performed only in two patients who did not respond to conservative management.